2011
DOI: 10.1007/s00383-011-2952-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical confirmation of the presence of smooth muscle in the normal neonatal anorectum and in neonates with anorectal malformations

Abstract: This preliminary work confirms the presence of smooth muscle in the anorectum of neonates that are normal and in neonates with anorectal malformations. It is likely that the smooth muscle complex demonstrated represents the internal anal sphincter in the normal anorectum. It is postulated that the smooth muscle complex seen in anorectal malformations may represent a similar internal anal sphincter complex which maybe of functional significance. Further IHC of tissue sections will allow reconstruction of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…There are few reports of IHC in the evaluation of smooth muscles in ARM. One study evaluated smooth muscle in relation to the anorectum in neonates that are normal and in neonates with ARM using immunohistochemical staining of antibodies specific to smooth muscle actin (SMA) . The presence of smooth muscle in the anorectum of ARM patients made authors postulate that smooth muscle complex seen may represent a similar internal anal sphincter complex, which maybe of functional significance.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports of IHC in the evaluation of smooth muscles in ARM. One study evaluated smooth muscle in relation to the anorectum in neonates that are normal and in neonates with ARM using immunohistochemical staining of antibodies specific to smooth muscle actin (SMA) . The presence of smooth muscle in the anorectum of ARM patients made authors postulate that smooth muscle complex seen may represent a similar internal anal sphincter complex, which maybe of functional significance.…”
Section: Discussionmentioning
confidence: 99%
“…A functional IAS in anorectal manometry, as indicated by a positive rectoanal inhibitory reflex, has been associated with improved functional outcomes in children who have high or intermediate ARMs by certain researchers (Husberg et al, 1997;Kyrklund et al, 2017). Animal models of ARMs have shown dysplastic IAS with variability in shape and size (Cleeve et al, 2011). Studies reported that the intrinsic muscle layers or the muscle in total are characteristically abnormal and hypoplastic in neonates with high type ARMs (Meier-Ruge and Holschneider, 2000).…”
Section: What About the Internal Anal Sphincter?mentioning
confidence: 99%
“…Studies reported that the intrinsic muscle layers or the muscle in total are characteristically abnormal and hypoplastic in neonates with high type ARMs (Meier-Ruge and Holschneider, 2000). Functional studies in children with different levels of ARM demonstrated an intact postoperative recto-anal inhibitory reflex (Cleeve et al, 2011). A smooth muscle layer can also be seen close to the opening of the fistula from the rectum to the urogenital tract (Husberg et al, 1997).…”
Section: What About the Internal Anal Sphincter?mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous approaches have attempted to overcome the problem of detaching tissue sections during HIAR treatment by using so-called “gentle” HIAR protocols 5,6 in which lower temperatures (approximately 70C), but considerably extended heating times (several hours), are applied. Standard HIAR protocols apply temperatures of approximately 90C to 100C and heating times <30 min, 1 with the aim to avoid the high temperature peaks that are a major cause of section detachment.…”
Section: Introductionmentioning
confidence: 99%